Therapeutic servicescapes and caregiver consumer journeys: a path toward transformative services - Furtado, Wilderson Moisés (2025)
Care is a multifaceted concept explored across philosophical, practical, and disciplinary boundaries (Aung et al., 2021; Togel et al., 2024), encompassing human states, moral ideals, affective experiences, relationships, and interventions (Morse et al., 1990; Turkel et al., 2018). In services marketing, it extends to care models, caregiving perspectives, and transformative service research (TSR), evolving beyond traditional caregiving contexts (Davey et al., 2023; Leino et al., 2021). Despite extensive exploration, a gap persists in understanding caregivers perceptions of their own well-being in service environments (Davey et al., 2023). Through an autoethnography perspective, this dissertation addresses this gap through three studies guided by the question: How does care influence the well-being and perceptions of vulnerability among sighted guides assisting visually impaired athletes in road-running events? The first study organizes existing research on care in services marketing. It highlights that care practices, such as promoting consumer well-being, enhance consumer experiences by fostering humanized, transformative service approaches. Integrating concepts like transformative service mediators (TSMs) enriches caring science beyond healthcare (Morse et al., 1990; Turkel et al., 2018). The second study explores sighted guides experiences as caregivers in road-running events, examining their well-being within therapeutic servicescapes. Findings reveal critical gaps in traditional service frameworks, particularly concerning accessibility and consumer security. Caregivers prioritize the well-being of those they support, underscoring the need for inclusive, secure services (Rosenbaum et al., 2020). The third study focuses on caregivers\' perceptions of their own well-being, analyzing their journeys as TSMs and consumers in road running. It reveals how care recipients\' vulnerabilities, coupled with service deficiencies, exacerbate caregivers \"secondary vulnerability.\" However, tools like self-spoken service language can mitigate these effects, contributing to discussions on vulnerability (Wilson-Nash, 2022), spoken service language (Scerri & Presbury, 2023), and TSMs (Davey et al., 2023). Practically, the dissertation underscores the need for improved caregiving policies, optimized servicescapes, and strategies to address political and cultural challenges in services marketing. It highlights TSMs\' roles in enhancing service accessibility and the importance of support from service providers and governments. Actionable strategies include designing inclusive events, recognizing vulnerable groups, and improving infrastructure to mitigate both primary and secondary vulnerabilities. Overall, this dissertation advances the understanding of care and TSR in services marketing, offering insights into caregiving policies, therapeutic servicescapes, and consumer journeys. It proposes strategies to improve service accessibility, reduce vulnerabilities, and foster inclusive, supportive environments through collaboration among service providers, governments, and TSMs.